Dielectric, thermal, optical, and degradation characteristics of MgO/ZnO-containing phosphate glasses - Khor, Shing Fhan (2011)
Investigation was carried out on binary (MgO)xCP20S)I-x with x = 20, 25, 30, 35, 40, 45 and 50 mol % and ternary senes (ZnO)30(MgO)xCP20s)7o-x, and 20 mol % in order to determine the role of zinc and magnesium ions in phosphate glasses. All the samples were prepared by traditional melt quenching technique. X-ray diffraction (XRD) measurement confirmed that the samples were amorphous. Dielectric spectroscopy, laser flash technique, differential thermal analyzer (DTA) , UV -visible spectrophotometer, ellipsometry and inductively coupled plasma-optical emission spectrometry (Iep-OES) have been used to characterize the electrical, thermal, optical features and ion released concentration respectively as well as to shed further light on the structure of the glasses. The dielectric permittivity (E') and loss factor (En) Were measured in the frequency range of 0.01 Hz to 1 MHz and in the temperature range between 303 and 573 K. The empirical data were sufficiently fitted and modeled with a superposition of Harviliak-Negami (HN) dielectric relaxation functions and a conductivity term. The results showed that the dielectric constant and dielectric loss factor decreased with frequency and increased with temperature. These interesting variations have been explained in the light of polarization and ionic interaction. At low frequencies, the dielectric loss factor spectrum was dominated by de conduction which was manifested by the 1/0) slope. Activation energy of dielectric relaxation (Em) was in the range 0.05 to 0.14 eV, 0.40 to 0.51 eV, 0.05 to 0.11 eV and 0.06 to 0.09 eV for binary glasses (MP) and ternary glasses with constant mole fraction of zinc (CZ), mangnesium (CM) and phosphate (CP), respectively. Activation energy of de conduction (Ecr) was in the range 1.00 to 1.15 eV, 1.04 to 1.16 eV, 0.92 to 1.07 eV and 1.06 to 1.12 eV for MP, CZ, CM and CP glass systems, respectively. The values of Ecr is higher than those for Em which suggest both the conduction and relaxation processes are due to different mechanisms. Thermal diffusivity measurements were carried out, in the temperature range of ambient to 573 K. The values decreased from 0.32 to 0.23 mm2/s. The response was explained based on phonon mean free path. The greater the network connectivity the greater the phonon mean free path which makes it easier for the phonon to propagate and eventually lead to higher values of thermal diffusivity. The glass transition temperature (TJ of the glasses was measured by DTA from 25 DC to 700 DC and the values of Tg was found in the range of 396 to 544 DC. The variation is proportional to the length of' phosphate chain, cross-linking density and bonding strength of the structure. The decreases in Tg reflects the bond strength of the glass structure is weakened on account of the rupture of phosphate cross-linked network. The UV spectra of the glasses were measured in the wavelength range of 190 to 1100 nm at ambient temperature. The Urbach rule was applied to evaluate the values of optical energy band gap (Eopt) and Urbach energy (Eu) for all the samples from the absorption spectrum. The Eopt was found to be in the range of3.64 to 3.78 eV, 3.36 to 3.44 eV, 3.47 to 3.79 eV and 3.54 to 3.81 eV for MP, CZ, CM and CP glass systems, respectively. Meanwhile Eu was found to be in the range 0.26 to 0.28 eV, 0.29 to 0.47 eV, 0.27 to 0.32 eV and 0.27 to 0.45 eV for MP, CZ, CM and CP glass systems, respectively. The behavior of both Eopt and Eu was correlated with structural disorder in the sample. As the non-bridging oxygen sites increase in the glassy matrix the valence bands were broadened resulting in a lower Eopt and higher Eu. Refractive index of the glasses was measured at ambient temperature with helium-neon laser of 632.8 nm wavelengths. The measured refractive index was found varying in between 1.508 and 1.575 and was dependent on the amount of non-bridging oxygen which has higher polarizability than bridging oxygen. This is because the depolymerization effect brought about retardation of light propagating through the phosphate network. The refractive index was found to vary proportionally with density as well. Chemical durability of the studied glasses has also been investigated in acidic, neutral and basic buffer solutions for 30 days to express the resistance offered by a glass towards attack by aqueous solutions. In the corrosion test, all the glass specimens experienced hydration, hydrolysis and precipitation steps. The dissolution rate (DR) of these glasses was in the range of 10-6 to 10-8 g/cm2 min and subjected to the relative concentration of Zn2+or Mg2+ions and glass compositions. The binary compositions exhibit excellent chemical durability which is comparable to window glass. The surface morphology of the CZ glass system was found to be the most affected by the buffer solutions on account of the formation of asymmetric bridging oxygen which tend to accelerate the hydrolysis process once the surface is hydrated. The pH values of all the solutions decreased as a function of time and this was attributed to the release of phosphate species from the dissolving glasses and subsequently the formation of phosphoric acid in the solution. Ion released measurement showed that all ions in the glass structure leached out of the glass surface when reacted in an aqueous solution. In addition, the ion leaching concentration strongly depended on the glass composition and the pH of the aqueous solution.